A Case Report on the Dramatic Response of 177Lu-PSMA Therapy for Metastatic Prostate Cancer - Erdogan, Aysenur Sinem; Sayan, Haluk; Seven, Bedri; Okudan, Berna (Current Medical Imaging, 2025)
Introduction:In nuclear medicine, Prostate-specific Membrane Antigen (PSMA) is a potential target for theranostics. Offering superior diagnostic accuracy to conventional imaging in prostate cancer (PCa), Gallium-68 labeled PSMA (68Ga-PSMA) positron emission tomography/computed tomography (PET/CT) is considered the new standard of care in PCa management. Tumor cells identified as PSMA-avid on PET/CT imaging can be targeted and eliminated with PSMA-labeled Lutetium-177 (177Lu-PSMA) therapy.Case Presentation:A sixty-eight years old patient who had metastatic castration-resistant PCa was reported in this study. Prior to receiving 177Lu-PSMA therapy, the patient’s PSA level was 358 ng/ml, and experienced extensive bone discomfort. Following ten cycles of 177Lu-PSMA therapy, exceptional results were observed.Conclusion:177Lu-PSMA therapy is likely to result in significantly better outcomes if first- or second-line treatments preserve the patient's bone marrow reserve or if the therapy is administered at earlier stages of the disease.
Keywords: Prostate-specific membrane antigen